Complement Evasion Protects FCoV from Virus Clearance Within Prototypic FIP Lesions - Anne Hönl; Sandra Felten; Katharina Erber; Michèle Bergmann; Sven Reese; Regina Hofmann-Lehmann; Marina L. Meli; Andrea M. Spiri; Katrin Hartmann; Kaspar Matiasek (Viruses)
Feline infectious peritonitis (FIP) is a fatal disease in cats caused by infection with feline coronavirus (FCoV). Despite severe inflammatory changes, defense mechanisms fail to achieve virus clearance. Some studies focused on various immune evasion mechanisms, but none of these studies elucidated the inefficacy of the complement system, which is one major player in FIP-associated immune pathogenesis. This study aimed to investigate the involvement of complement-regulating factors (CRFs). CRFs help modulate the immune response and prevent host tissue damage. Archived tissue samples from 31 deceased, FIP-affected cats were evaluated using multiplex immunohistochemistry for the spatial expression of the complement-regulating factors CD46 and CD59 in association with FIP lesions and their colocalization with complement-activating factor C1q and membrane attack complex C9 in relation to the presence and proximity of FCoV-infected cells. The FIP lesions of all 31 cats exhibited marked expression of both complement-regulating factors in proximity to FCoV-infected macrophages. Moreover, their expression in all 31 animals was significantly lower than the expression of the complement-activating factors C1q and C9 compared to areas farther distal to FCoV-infected cells. In conclusion, FCoV-infected macrophages in cats with FIP appear to use autocrine and paracrine expression of complement-regulating factors in their immediate environment to shield themselves from destruction by the complement system.